Study of radiation-resistant gel bases for composite detectors - Boyarintsev, A.Yu.; Galunov, N.Z.; Karavaeva, N.L.; Krech, A.V.; Lazarev, I.V.; Levchuk, L.G.; Nepokupnaya, T.A.; Panikarskaya, V.D.; Popov, V.F.; Sorokin, P.V.; Tarasenko, O.A. (Functional Materials, 2013)
Light transmittance T of the commercially available dielectric gels as a function of integrated radiation dose D was studied in this work. Irradiation of samples was performed by electron accelerator with integrated radiation doses up to 90 Mrad. It allowed choosing the gels for development of radiation-resistant detection systems on their base. It was shown that dielectric gels Sylgard-184 and Sylgard-186 are the most suitable for this purpose due to their mechanical and optical characteristics.